Iron Age metal working in the Magaliesberg area - H. M. Friede (The Southern African Institute of Mining and Metallurgy, 1977)
Iron Age metal working in the Magaliesberg area by H. M. FRIEDE, Ph.D. (Visitor) Evidence of smelting and metal working in the Magaliesberg comes mainly from three sites: Broederstroom (Pretoria District). Uitkomst Cave (Krugersdorp District), and Olifantspoort/Olifantshoek \Rustenburg District). The analyses of copper ores found at or near these sites are reported. as are the analyses of twenty-six samples of slag from the Magaliesberg area and other sites in the Transvaal. Iron implements and copper ornaments found at the Magaliesberg sites are described. and the analyses of some of these specimens are reported and discussed. A metallographic report on two iron objects from Broederstroom points to similarities in the smelting and forging techniques that were practised in the Transvaal and Nigeria during the Early Iron Age.